(untitled) (KYAMC Journal, 2024)
Background: Rapid motorization bought a boon along with the curse of road traffic accidents toll. Injuries and death due to RTA are one of the major public health problems across the globe, especially in developing countries, due to lack of comprehensive legislative measures. RTA are responsible for the greatest number of injuries and fatalities worldwide by killing around 1.2 million people each year and injuring another 50 million. It will have an immeasurable impact on the families affected by RTA. Objective: To evaluate the situation of RTA in Tangail and to find out the pattern of injuries present in the dead bodies in RTA. Materials and Methods: This is a retrospective study based on autopsy reports conducted to find out the pattern of death due to road traffic accidents in Sheikh Hasina Medical College and Hospital, Tangail during the period from 1st January 2020 to 31st December 2020. After reviewing all postmortem reports 53 cases were found due to RTA, including railway accidents during this study period. Results: A total of 391 postmortem were conducted during the study period from January 2020 to December 2020 and out of which 53 cases were RTA. Female deaths were only 12( 22.64%) and the majority of the deaths were male 41( 77.36%). The highest percentage of deaths were found in the age group 21-30 year 21( 39.62%), followed by 31-40 (18.87%), 41-50 years( 16.98%). According to the types of vehicles, buses and lorries were responsible for the deaths. Regarding the types of victim distribution, pedestrians 28 (52.83(%) were the highest percentage and vehicle occupants were 15(28.30%). Among total cases, head injury (41.51%) was the highest percentage responsible for deaths, followed by fracture of the skull bone ( 41.51%), fracture of the long bone ( 16.98%), chest injuries( 22.64%) and pelvis fracture (5.66%.) Conclusion: Strict enforcement of traffic law, using seatbelts, maintaining the fitness of vehicles, driving licenses, improving public awareness, etc., can reduce this economic burden and protect vulnerable groups of people in our country. KYAMC Journal Volume: 14, No: 03, October 2023: 158-160.